High risk cutaneous squamous cell carcinoma of the head and neck - Stephen Y. Kang (KeAi Communications Co., Ltd., 2016)
The majority of patients with head and neck cutaneous squamous cell carcinoma (cSCC) are successfully treated with surgical treatment of the primary site. While only a minority of patients is at risk for regional metastasis, these patients have significantly worse outcomes. Tumor and patient factors that place patients at high risk for development of regional metastasis have been identified. Advancing treatment of cSCC requires identifying and escalating treatment in this high risk patient population, while avoiding overtreatment of the majority of cSCC patients that do not develop regional metastasis. Sentinel lymph node biopsy has emerged as a promising technique in cSCC to detect micrometastasis and allow early surgical treatment of regional disease. Future directions involve genomic characterization of metastatic and nonmetastatic cSCC to identify genomic alterations causing metastasis that may be used to predict disease behavior. Keywords: Squamous cell carcinoma, Cutaneous, Head and neck cancer